A new language for traumatic experience: From dissociation–enactment to the fracturing of embodied wholeness. (3rd July 2021) - Sletvold, Jon; Brothers, Doris
Abstract: When viewed from the vantage point of embodiment, the psychoanalytic understanding of traumatic experience is transformed. In this article, a new language is proposed that describes traumatic experience as disturbances in the flow of an individual's effortless, unconscious focusing on oneself ("I"), the other or others ("you"), on oneself as connected to others ("we"), and on all that involves the nonhuman surround ("world"). From this perspective, developmental and late-onset trauma models are seen as overlapping rather than competing. The authors support their proposal by drawing on self psychology, relational theory, and the Boston Change Process Study Group and offer illustrative clinical material.